TPT sulfonate, a single, oral dose schistosomicidal prodrug: In vivo efficacy, disposition and metabolic profiling. Issue 3 (December 2018) - Wolfe, Alan R.; Neitz, R. Jeffrey; Burlingame, Mark; Suzuki, Brian M.; Lim, KC; Scheideler, Mark; Nelson, David L.; Benet, Leslie Z.; Caffrey, Conor R.
Abstract: Treatment of schistosomiasis relies precariously on just one drug, praziquantel (PZQ). In the search for alternatives, 15 S-[2-(alkylamino)alkane] thiosulfuric acids were obtained from a previous research program and profiled in mice for efficacy against both mature (>42-day-old) and juvenile (21-day-old) Schistosoma mansoni using a screening dose of 100 mg/kg PO QD x4. One compound, S -[2-( tert -butylamino)-1-phenylethane] thiosulfuric acid (TPT sulfonate), was the most effective by decreasing female and male worm burdens by ≥ 90% and ≥46% (mature), and ≥89% and ≥79% (juvenile), respectively. In contrast, PZQ decreased mature female and male worm burdens by 95% and 94%, respectively, but was ineffective against juvenile stages. Against 7-day-old lung-stage worms, TPT sulfonate was only effective at twice the dose decreasing female and male burdens by 95 and 80%, respectively. Single oral doses at 400 and/or 600 mg/kg across various developmental time-points (1-, 7-, 15-, 21- and/or 42 day-old) were consistent with the QD x4 data; efficacy was strongest once the parasites had completed lung migration, and female and male burdens were decreased by at least 90% and 80%, respectively. In vitro, TPT sulfonate is inactive against the parasite suggesting a pro-drug mechanism of action. In mice, TPT sulfonate is fully absorbed and subject to rapid, non-CYP-mediated, first-pass metabolism that is initiated by desulfation and yields a series of metabolites. The initially-formed free thiol-containing metabolite, termed TP thiol, was chemically synthesized; it dose-dependently decreased S. mansoni and Schistosoma haematobium motility in vitro . Also, when administered as a single 50 mg/kg IP dose, TP thiol decreased 33-day-old S. mansoni female and male burdens by 35% and 44%, with less severe organomegaly. Overall, TPT sulfonate's efficacy profile is competitive with that of PZQ. Also, the characterization of a parasiticidal metabolite facilitates an understanding and improvement of the chemistry, and identification of the mechanism of action and/or target. Graphical abstract: Image 1 Highlights: TPT sulfonate provides single dose efficacy that is competitive with the current drug, praziquantel. TPT sulfonate must be biotransformed to be active. TPT sulfonate is fully absorbed and subject to rapid, non-CYP-mediated, first-pass metabolism. One of the key metabolites, TP thiol, is anti-schistosomal in vitro and in vivo .